ANALYSIS OF POPULATION GROWTH, CARBON EMISSION, AND RENEWABLE ENERGY NEXUS IN NIGERIA - EZE, UCHECHUKWU; UGWUOKE , CORNELIUS CHINEMEOGO (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study investigated the impact of population growth and Carbon emission: a study on the contribution of renewable energy in Nigeria from 1990 to 2023 employing the Autoregressive Distributed Lag (ARDL) modeling. Some of the variables used in the analysis included population growth (POG), renewable energy consumption (REC), carbon emission (C02), real gross domestic product (RGDP), trade (TO), fossil fuel consumption (FFC), and gross fixed capital formation (GFCF). As discussed, the impact analysis of the independent variable on Carbon emission (C02) shows that population growth has long-run positive impacts on Carbon emissions (C02), and renewable energy hurts Carbon emissions. As for the other variables such as RGDP and FFC, they also were found to have a negative and significant relationship with the level of carbon emission in Nigeria in the short-run and long-run. On the other hand, variables like GFCF and To have no significant influence on Carbon emission (C02). Accordingly, the following policy recommendation is made: Nigerian government policies should assist in enhancing the uptake of renewable energy in Nigeria to reduce carbon emissions that are hazardous to the lives of the country's people and the effectiveness of the ozone layer. Further, production facilities needed to boost renewable energy consumption in the country like solar, electricity vehicles, etc. must be manufactured there.